Sagittal alignment of spine and pelvis in asymptomatic adults: norms in Chinese populations - Zhu, Zezhang; Xu, Leilei; Zhu, Feng; Jiang, Long; Wang, Zhou; Liu, Zhen; Qian, Bang-ping; Qiu, Yong (Spine (Philadelphia, Pa. 1976), 2014)
A prospective, cross-sectional study. To investigate the normal values of sagittal spinal and pelvic parameters in Chinese populations and to determine the influence of age, sex, weight, and ethnicity on variations of these parameters. A few studies have been conducted to evaluate the morphology and orientation of pelvis in asymptomatic adults of Caucasian populations. However, there is still a lack of investigation concerning the normal range of spinal and pelvic alignment in Asian populations. A cohort of 260 asymptomatic adult volunteers from Chinese Han populations was prospectively recruited. The following 6 radiological parameters on lateral radiograph were evaluated for each subject, including sacral slope (SS), pelvic tilt, pelvic incidence, thoracic kyphosis, lumbar lordosis, and C7 tilt. Comparisons of these parameters between the male and the female and between Chinese Han populations and Caucasian populations were carried out with Student t tests. The relationships between all parameters and age and weight were assessed using the Pearson correlation analysis. The mean values of spinopelvic parameters of the cohort were 44.6 ± 11.2° for pelvic incidence, 11.2 ± 7.8° for pelvic tilt, and 32.5 ± 6.5° for SS, respectively. With the age matched, subjects from Chinese populations were found to have significantly smaller pelvic incidence and SS than those from Caucasian populations. The females were found to have significantly higher lumbar lordosis than the males. Presenting significant but small correlations with age of both male and female adults, thoracic kyphosis and pelvic tilt tended to increase with age, whereas SS had a tendency to decrease with age. Weight was significantly correlated with thoracic kyphosis, SS, and lumbar lordosis. The normal values of sagittal spinal and pelvic parameters in Chinese populations could be significantly influenced by age, weight, and sex. Moreover, obvious variations of spinopelvic parameters were found between populations with different ethnicity background. N/A.